Knowing the Great Plains Weather: Field Life and Lay Participation on the American Frontier during the Railroad Era. Issue 2 (1st June 2019) - Vetter, Jeremy
Abstract: On the US Great Plains frontier in the late nineteenth century, perhaps no area of scientific knowledge was more contested than the weather, which connected with debates around the long-term climate of this semiarid region. Observation of the weather was shared across the divide between scientists and lay people, illustrating an early historical predecessor of enlisting citizen scientists to help in the production of knowledge. Situating this example of lay participation in the larger context of diverse modes of field practice during the railroad era, this article examines the production of weather knowledge on the Great Plains frontier, especially in Kansas, to explore some important stages in the process of coordinating lay observers, including the ground-level practices of organizing lay people into networks for producing knowledge, and marginalizing and discrediting folk knowledge about the weather that was autonomous from the authorized scientific community. The author argues for greater attention to the historical emergence of crucial hierarchical, structured aspects of lay participation in science, inflected by the Chinese concept of shi, in contrast to the recently common focus on flattened, collaborative networks.